Forest of Secrets - Hunter, Erin. (New York : Avon Books, 2004)
The warrior cat Fireheart's determination to uncover the truth about another warrior's death leads him deep into danger, and reveals secrets that test the strength of clan loyalties.
5.5
5-8
Keywords: Cats -- Fiction; Fantasy; Cats -- Fiction; Fantasy fiction